Amphiregulin and ocular axial length - Dong, Li; Jonas, Jost B. (Acta ophthalmologica, 2019)
Purpose To assess the potential role of amphiregulin as messenger molecule in ocular axial elongation. Methods The experimental study included guinea pigs (total n = 78) (age: 3-4 weeks) which underwent bilateral lens-induced myopization and received 15 days later three intraocular injections in weekly intervals of amphiregulin antibody (doses:5 μg, 10 μg, 20 μg) into their right eyes, and three phosphate-buffered saline injections into their left eyes; and guinea pigs without lens-induced myopization and which received three unilateral intraocular injections of amphiregulin antibody (dose: 20 μg) or amphiregulin (doses: 1 ng; 10 ng; 20 ng) into their right eyes, and three phosphate-buffered saline injections into their left eyes. Seven days later, the animals were sacrificed. Intravitally, we performed biometry, and histology and immunohistochemistry post-mortem. Results In animals with bilateral lens-induced myopization, the right eyes receiving amphiregulin antibody showed reduced axial elongation in a dose-dependent manner (dose: 5 μg: side difference: 0.14 ± 0.05 mm;10 μg: 0.22 ± 0.06 mm; 20 μg: 0.32 ± 0.06 mm; p < 0.001), thicker sclera (all p < 0.05) and higher cell density in the retinal nuclear layers and retinal pigment epithelium (RPE) (all p < 0.05). In animals without lens-induced myopia, the right eyes with amphiregulin antibody application (20 μg) showed reduced axial elongation (p = 0.04), and the right eyes with amphiregulin injections experienced increased (p = 0.02) axial elongation in a dose-dependent manner (1 ng: 0.04 ± 0.06 mm; 10 ng: 0.10 ± 0.05 mm; 20 ng: 0.11 ± 0.06 mm). Eyes with lens-induced axial elongation as compared to eyes without lens-induced axial elongation revealed an increased visualization of amphiregulin upon immunohistochemistry and higher expression of mRNA of endogenous amphiregulin and epidermal growth factor receptor, in particular in the outer part of the retinal inner nuclear layer and in the RPE. Conclusion Amphiregulin may be associated with axial elongation in young guinea pigs.
Gesehen am 14.05.2019